PENDAMPINGAN PEMBELAJARAN DARING TERHADAP PESERTA DIDIK SD/MI DI DESA GUCI DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN INTERAKTIF - Nur Zaini,; Nikmatul Khori, (TAAWUN, 2021)
Indonesia confirmed the spread of Covid-19 since the beginning of March 2020. Until now, this virus has had an impact on almost all areas of life, not only health but also the economy, especially education. In the field of education, the government implements regulations regarding online learning systems or Distance Learning (PJJ) by means of Study From Home (Learning From Home). Online learning is a new thing for educational institutions. Many obstacles that occur include the teacher still having difficulty in determining the use of appropriate media for international learning. Another obstacle is the lack of parental assistance. Therefore, the authors conducted online learning assistance for SD / MI students using interactive learning media. Researchers used mentoring strategies and the methods used were online and offline methods. The result of the mentoring process using interactive learning media is the increased interest, motivation and achievement of students and this is an ineffective solution to online learning problems. There are many factors in the implementation of online learning assistance for SD / MI students in Guci village, both supporters and obstacles. Among the supporting factors are the talents, high interest and motivation of students, family support, school, community. The inhibiting factors are the lack of facilities or infrastructure used for learning both online and face-to-face, the lack of discipline of students during face-to-face mentoring, lack of discipline in using masks, and so on.